Early Childhood Development Programs in Nepal: Opportunities and Challenges - Dahal, Meenakshi (Journal of Productive Discourse, 2024)
This article presents a comprehensive examination of the contemporary landscape of Early Childhood Development (ECD) initiatives in Nepal, focusing on both their quality and accessibility. Through a meticulous analysis of secondary data, this study scrutinizes the current state of Early Childhood Education and Development (ECED) centers, the pivotal roles of educators, and the efficacy and caliber of ECD programs, thereby elucidating the prevailing opportunities and obstacles. A high-quality ECD program is fundamental in extending developmental prospects to all children, including those facing adversities, by furnishing them with requisite care, support, and safeguarding. Realizing this necessitates concerted efforts from diverse stakeholders, entailing heightened investments in ECD and the advocacy of its developmental imperatives. Paramount among these stakeholders is the family, serving as the primary gateway to ECD interventions, underscoring the imperative for tailored interventions within familial contexts. Moreover, communities wield significant potential in augmenting ECD initiatives. Thus, a decentralized approach to ECD delivery across all strata of governance emerges as imperative. The realization of quality ECD hinges upon the convergence of multifaceted inputs, harmonized across various domains. By fostering synergy among these inputs, ECD programs can achieve their utmost efficacy and impact, thereby fostering holistic child development.